Enhanced simulations of overland-gully-sewer flow interactions in coupled three-layer dual drainage modeling - Chia-Ho Wang; Hsiang-Lin Yu; Tsang-Jung Chang; Albert S. Chen (Journal of Hydrology, 2026)

Balancing efficacy and safety: Inorganic and organic Fe-Ca Co-interventions reduce oral Cd bioavailability from rice and their impacts on gut health - Xin-Ying Lin; Hong-Bo Li; Duo-Duo Jiao; Lu Zhou; Bo Xu; Albert Juhasz; Lena Q. Ma; Dongmei Zhou (Journal of Hazardous Materials, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Plasticity and regional heterothermy of upper thermal tolerance in the ring-necked snake - Christian L. Cox; Kelly Lin Wuthrich; Dareen Aloudeh; Samuel J. Baker; Anna G. Climo; Alexa F. Gross; Christian W. Kizer; Zoe M. Korff; Oscar Melendez Vera; Veronica Y. Silva; Alexis M. Spans; Grace R. Thilenius; et al. (Journal of Thermal Biology, 2026)

Sensitivity of thermal evapotranspiration models to surface and atmospheric drivers across ecosystems and aridity - Aolin Jia; Kanishka Mallick; Ziyu Lin; Mauro Sulis; Zoltan Szantoi; Lilin Zhang; Chiara Corbari; Pedro Torralbo Munoz; Hector Nieto; Jean-Louis Roujean; Jordi Etchanchu; Jerome Demarty; et al. (Agricultural and Forest Meteorology, 2026)

Traversing the Valley of Death for nanotechnology-based natural products: strategies and insights from pharmaceutical stakeholders - Jian Sheng Loh; Chan Yew Low; Wei Peng Low; Yun Lin Ng; Wen Qi Mak; Li Kar Stella Tan; Hong Hao Chan; Yong Sze Ong; Stephanie Kay Ann Cheah; Emmellie Laura Albert; Chee Wun How (Drug Delivery and Translational Research, 2025)

Sustainable high-flux ceramic membrane operations for seawater pretreatment under diverse algal bloom intensities - Boyan Xu; Meiyue Ding; Kar Ming Tan; Brenda Rui Lin Tan; Tze Chiang Albert Ng; Lai Yoke Lee; Noguchi Hiroshi; Niwa Terutake; Sungwoo Bae; How Yong Ng (Water Research, 2025)

Health risk assessment of dietary cadmium exposure based on cadmium bioavailability in food: Opportunities and challenges - Di Zhao; Guo-Bin Lin; Chenjing Liu; Albert L. Juhasz; Lena Q. Ma (Journal of Hazardous Materials, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Surgical Parameters During Reverse Shoulder Arthroplasty Predict Post-Surgical Kinematics During the Hand-to-Head Motion - Ajinkya A. Rai; Clarissa M. LeVasseur; Gillian E. Kane; Maria A. Munsch; Christopher J. Como; Alexandra S. Gabrielli; Jonathan D. Hughes; William J. Anderst; Albert Lin (Annals of Biomedical Engineering, 2025)

Microbial rrn copy number is associated with soil C: N ratio and pH under long-term fertilization - Xiu Wang; Jiahui Lin; Xinyi Peng; Yifan Zhao; Haodan Yu; Kankan Zhao; Albert Barberán; Yakov Kuzyakov; Zhongmin Dai (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Generating high spatial resolution exposure estimates from sparse regulatory monitoring data - Yihui Ge; Zhenchun Yang; Yan Lin; Philip K. Hopke; Albert A. Presto; Meng Wang; David Q. Rich; Junfeng Zhang (Atmospheric Environment, 2023)

Feasibility of a TDR-based technique for fluid hydrocarbon leak detection - Chih-Ping Lin; Yin Jeh Ngui; Yi-Pei Chan; Albert T. Yeung (Process Safety and Environmental Protection, 2023)

A callus-derived regeneration and Agrobacterium-mediated gene transformation developed for bilberry, Vaccinium myrtillus - Yanping Song; Wenbo Luo; Ying Wu; Xiaojie Li; Nick W. Albert; Yinhai Zhang; Xiangtao Chen; Kui Lin-Wang; Cecilia H. Deng; Zhubing Hu; Bingsong Zheng; Xiaofei Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Mechanism and multi-step kinetic modelling of Cr(VI) adsorption, reduction and complexation by humic acid, humin and kerogen from different sources - Samuel Barnie; Jia Zhang; Peter Appiah Obeng; Albert Ebo Duncan; Caspar Daniel Adenutsi; Lin Xu; Honghan Chen (Environmental Science and Pollution Research, 2021)

Experiments on gravity currents propagating on unbounded uniform slopes - Albert Dai; Yu-Lin Huang (Environmental Fluid Mechanics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Nitrogen footprints: Regional realities and options to reduce nitrogen loss to the environment - Hideaki Shibata; James N. Galloway; Allison M. Leach; Lia R. Cattaneo; Laura Cattell Noll; Jan Willem Erisman; Baojing Gu; Xia Liang; Kentaro Hayashi; Lin Ma; Tommy Dalgaard; Morten Graversgaard; et al. (Ambio, 2017)

Characterization and utilization of microsatellites in the Coffea canephora genome to assess genetic association between wild species in Kenya and cultivated coffee - Collins Ogutu; Ting Fang; Lin Yan; Lu Wang; Lifang Huang; Xiaoyang Wang; Baiquan Ma; Xianbao Deng; Albert Owiti; Aggrey Nyende; Yuepeng Han (Tree Genetics & Genomes, 2016)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

Unincorporated iron pool is linked to oxidative stress and iron levels in Caenorhabditis elegans - Natalie A. Rangel; Lawrence Lin; Kanyasiri Rakariyatham; Albert Bach; Kim Trinh; Matthew H. S. Clement; Chandra Srinivasan (BioMetals, 2012)

Characterization of the mechanical properties of bovine cortical bone treated with a novel tissue sterilization process - Nathan Kemper; Noel Davison; Daniel Fitzpatrick; Rebecca Marshall; Albert Lin; Katherine Mundy; Ronald R. Cobb (Cell and Tissue Banking, 2011)

InSAR detection of residual settlement of an ocean reclamation engineering project: a case study of Hong Kong International Airport - Qing Zhao; Hui Lin; Wei Gao; Howard A. Zebker; Albert Chen; Kin Yeung (Journal of Oceanography, 2011)

Learning Through Service: Student Perceptions on Volunteering at Interprofessional Hepatitis B Student-run Clinics - Leslie C. Sheu; Patricia Zheng; Anabelle D. Coelho; Lisa D. Lin; Patricia S. O’Sullivan; Bridget C. O’Brien; Albert Y. Yu; Cindy J. Lai (Journal of Cancer Education, 2011)

A GIS-based Decision Support System for Typhoon Emergency Response in Taiwan - Ming-Hsi Hsu; Albert S. Chen; Liang-Chun Chen; Cheng-Shang Lee; Feng-Tyan Lin; Chen-Jia Huang (Geotechnical and Geological Engineering, 2011)

Monoamine oxidase A gene polymorphisms and enzyme activity associated with risk of gout in Taiwan aborigines - Hung-Pin Tu; Albert Min-Shan Ko; Shu-Jung Wang; Chien-Hung Lee; Rod A. Lea; Shang-Lun Chiang; Hung-Che Chiang; Tsu-Nai Wang; Meng-Chuan Huang; Tsan-Teng Ou; Gau-Tyan Lin; Ying-Chin Ko (Human Genetics, 2010)

Early developmental and stress responsive ESTs from mungbean, Vigna radiata (L.) Wilczek, seedlings - Li-Ru Chen; Albert H. Markhart; S. Shanmugasundaram; Tsai-Yun Lin (Plant Cell Reports, 2008)

Comparative Physicochemical Characterization of Phospholipids Complex of Puerarin Formulated by Conventional and Supercritical Methods - Ying Li; Da-Jian Yang; Shi-Lin Chen; Si-Bao Chen; Albert Sun-Chi Chan (Pharmaceutical Research, 2008)

Cocaine increases human immunodeficiency virus type 1 neuroinvasion through remodeling brain microvascular endothelial cells - Milan Fiala; Amy J Eshleman; John Cashman; Justin Lin; Albert S Lossinsky; Vannina Suarez; Wendy Yang; Jun Zhang; Waldemar Popik; Elyse Singer; Francesco Chiappelli; Eva Carro; et al. (Journal of NeuroVirology, 2005)

The role of halogen substitution in classical cannabinoids: A CB1 pharmacophore model - Spyros P. Nikas; Jolanta Grzybowska; Demetris P. Papahatjis; Avgui Charalambous; Ali R. Banijamali; Ravi Chari; Pusheng Fan; Therapia Kourouli; Sonyuan Lin; Albert J. Nitowski; Gilbert Marciniak; Yan Guo; et al. (The AAPS Journal, 2004)

Temporal selectivity by single neurons in the torus semicircularis of Batrachyla antartandica (Amphibia: Leptodactylidae) - Mario Penna; Wen-Yu Lin; Albert Feng (Journal of Comparative Physiology A, 2001)

Sphingolipids as biomarkers of fumonisin exposure and risk of esophageal squamous cell carcinoma in China - Christian C. Abnet; Craig B. Borkowf; You-Lin Qiao; Paul S. Albert; Elaine Wang; Alfred H. Merrill; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Free-field unmasking response characteristics of frog auditory nerve fibers: comparison with the responses of midbrain auditory neurons - Wen-Yu Lin; Albert Feng (Journal of Comparative Physiology A, 2001)

Autosomal dominant macrothrombocytopenia with leukocyte inclusions (May-Hegglin anomaly) is linked to chromosome 22q12-13 - Michael J. Kelley; William Jawien; Albert Lin; Karen Hoffmeister; Elizabeth W. Pugh; Kimberly F. Doheny; Jeannette F. Korczak (Human Genetics, 2000)

Autosomal dominant macrothrombocytopenia with leukocyte inclusions (May-Hegglin anomaly) is linked to chromosome 22q12-13 - Michael J. Kelley; William Jawien; Albert Lin; Karen Hoffmeister; Elizabeth W. Pugh; Kimberly F. Doheny; Jeannette F. Korczak (Human Genetics, 2000)

Temporal selectivity for complex signals by single neurons in the torus semicircularis of Pleurodema thaul (Amphibia: Leptodactylidae) - Mario Penna; Wen-Yu Lin; Albert S. Feng (Journal of Comparative Physiology A, 1997)